The Effect of Climate Change on Firm Level Costs with Focus on MENA Region - Saieed, Farah Osama (AUC Knowledge Fountain, 2022)
This paper has a main objective of identifying the relationship between environmental factors and climate change on operating costs incurred by firms. This paper also attempts to compare the direction and intensity of the effect on different sectors in order to analyze whether climate change effect differs based on the nature of the business operations. Several papers have previously addressed the relationship between climate change factors ad profits. This literature will add to previous studies by observing the effect on the cost rather than the profits. In addition to providing results that minimize endogeneity, which is found in a large scale in this particular relationship. This will enable us to test whether some sectors are positively affected (incur lower costs) by the deterioration in the environment and the worsening of climate conditions and climate change severity. Our initial hypothesis predicts that in general, overall firms will incur higher costs due to climate change disruptions and the need to adjust operations accordingly. The study results can be summarized as following: Overall climate change conditions result in a direct increase in costs on firms operating in the MENA region. When observing sectors, we have found that sectors which are most linked and dependent on natural resources and land quality are those highly impacted by the variable changes. Meanwhile, firms with less dependency on natural resources and are rather more technologically built, have a weaker relationship and significance with climate changes. This study encourages firms’ and the MENA region as a whole to reconsider regulations and measures taken to overcome or rather to manage the increasing climate change threats imposed due to the severity of their consequences.